Analytical model for simulating thin-film/wafer-based tandem junction solar cells. (1st July 2017) - Davidson, Lauren; Haque, K.A.S.M. Ehteshamul; Toor, Fatima
Highlights: Matlab-based analytical model capable of modeling wafer-based and thin-film tandem solar cells. Comparison of device performance for series versus n-terminal tandem solar cells. Design of a perovskite and black Silicon (bSi) tandem cell with an efficiency greater than 30%. Abstract: Replacing the present-day commercial single junction silicon (Si) solar cells with low cost, high efficiency solar cells is imperative, in order to compete with other existing energy technologies. Many research groups have looked into using III–V materials, tandem junction solar cells and thin-film technologies to reach higher efficiencies. However, many of these techniques involve expensive materials or costly manufacturing processes. In this research, we focus on a tandem junction solar cell design that is based on a thin-film perovskite top cell and wafer-based Si bottom cell. In order to analyze the performance of the tandem cell, an analytical model is needed to compute the quantum efficiency and characteristic solar cell data. The highly versatile Matlab-based analytical model presented in this work is capable of modeling different kinds of tandem cells based on a variety of solar absorber combinations. The model allows user to adjust input parameters, such as reflectivity, material thickness, donor and acceptor densities, and carrier lifetimes in order to optimize the quantum efficiency, maximum power output, open circuit voltage, and short circuit current quantities of the cell. Using this analytical model, we were able to design a perovskite and black Silicon (bSi) tandem cell, which reached an efficiency of greater than 30%.